Exploring the digital space as a site of literary creation - Gora, Tatenda (Midlands State University, 2019)
Advancements in technology in the 21st century have of late revolutionized the business industry, communication and social life as a whole. This has been made possible by various digital media platforms, the most popular being Facebook and Whatsapp. The field of literature seems to be no exception as there is material of a literary nature on these digital media platforms. This study intends to demonstrate how with the rise of digital media platforms literary production has been revolutionized and democratized. To achieve this, the study draws examples of literary texts circulating on Facebook and Whatsapp. It also goes on to look at the genres, style and thematic concerns of the literary texts circulating on digital media platforms. Ethical issues posed by self published literature and intellectual property issues are at the core of this study as these texts do not go through the publishing process. The research is informed by the Uses and Gratifications theory which propounds that the use of particular media is determined by need. It is as a result of needs gratification that new media technologies have become popular as compared to the traditional media as research has shown that people now spend most of their time on these new sites. It emerges in this study that digital media platforms especially Facebook and Whatsapp offer quite a number of needs as compared to the television and the radio. The fact that social media platforms are not censored has also contributed to the popularity of these platforms as they promote freedom of expression. Circulating on social media platforms are novels, poems, short stories and other material. Digital media platforms have revolutionized literary production in the sense that literary texts can now be accessed online easily, sometimes free of charge. However these platforms can be a threat to our culture and unity as a nation because anyone is free to post anything without sometimes even considering the implications of the content on the next person.